Artful Relation: Buñuel's Debt to Galdós in Nazarín and Tristana. - Faulkner, Sally (Hispanic Research Journal, 2003)
This article combines a theoretical consideration of the narrator in film fiction with a specific analysis of Luis Buñuel's cinematic adaptations of Benito Pérez Galdós's novels Nazarín (1958/1895) and Tristana (1970/1892). Previous interpretations of these film adaptations have tended to regard the literary originals as incidental to Buñuel's auteurist vision. A formal analysis of Nazarín and Tristana reveals, however, a remarkable similarity between Buñuel and Galdós in terms of narrative enunciation. This study contends that the striking plurality of critical responses to Buñuel's work is encoded in the equivocal nature of his filmic narration. It argues furthermore that the formal ambiguity of Buñuel's films derives from the novels of Galdós and that the adaptations of Nazarín and Tristana foreground this debt. With reference to Bruce Kawin's model of cinematic subjectivity elaborated in his Mindscreen (1978), the article demonstrates that the ironic, unreliable narrators of Galdós's novels are creatively imitated by Buñuel in the filmic medium. Ambiguous narration thus reveals Galdós's and Buñuel's shared challenges to realism.